IMPACT OF MICRO FINANCE ON THE WOMEN EMPOWERMENT - Thangjam Ravichandra (International Journal of Research in Finance & Marketing, 2014)
This study is concerned to find the impact of microfinance schemes on women empowerment, in terms of changes in income, savings, socio-economic status, and political participation. The study was conducted on a sample of 220 women beneficiaries of microfinance services of a leading MFI operating in Kerala state and the sample was selected by multi-stage cluster sampling. The results of the study show that microfinance programs have created a positive impact to its beneficiaries. Majority of the respondents are engaged in various income generating activities because of the credit facilities provided by microfinance institutions. This resulted in a significant change in their income level and savings after participating in microfinance programs. This has helped them to earn income for their family and also enabled them to play an important role in their family and also in society.